2013
DOI: 10.1088/0004-637x/773/1/26
|View full text |Cite
|
Sign up to set email alerts
|

The Size, Shape, Albedo, Density, and Atmospheric Limit of Transneptunian Object (50000) Quaoar From Multi-Chord Stellar Occultations

Abstract: We present results derived from the first multi-chord stellar occultations by the transneptunian object (50000) Quaoar, observed on 2011 May 4 and 2012 February 17, and from a single-chord occultation observed on 2012 October 15. If the timing of the five chords obtained in 2011 were correct, then Quaoar would possess topographic features (crater or mountain) that would be too large for a body of this mass. An alternative model consists in applying time shifts to some chords to account for possible timing erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 37 publications
(70 reference statements)
1
60
0
Order By: Relevance
“…It appears to be a particularly fascinating object in the outer solar system with an estimated density of 1.99 ± 0.46 g cm −3 derived from the first multi-chord stellar occultations by Braga-Ribas et al (2013), which is significantly lower than the one proposed by Fraser et al (2013a), and it agrees with the determination by Fornasier et al (2013) estimated on the basis of the new Herschel far-IR data.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…It appears to be a particularly fascinating object in the outer solar system with an estimated density of 1.99 ± 0.46 g cm −3 derived from the first multi-chord stellar occultations by Braga-Ribas et al (2013), which is significantly lower than the one proposed by Fraser et al (2013a), and it agrees with the determination by Fornasier et al (2013) estimated on the basis of the new Herschel far-IR data.…”
Section: Introductionsupporting
confidence: 80%
“…Braga-Ribas et al (2013) reported a preferred solution for the effective diameter of 1111 ± 5 km obtained from a multichord stellar occultation. The size of (50000) Quaoar is comparable to Pluto's moon Charon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we compare our results as well as our technique for deriving this information from the light curve with other methods. In fact, the density, albedo and/or sizes of both components can also be obtained from other methods, such: i) thermal or thermophysical modeling based on data obtained, for example, with the Herschel Space Observatory or the Spitzer Space Telescope Stansberry et al 2008); ii) from the mutual orbit of the binary component Brown et al 2010); iii) from direct imaging (Brown & Trujillo 2004), or iv) from stellar occultation by (B)TNOs (Sicardy et al 2011;Braga-Ribas et al 2013). However, these methods only provide some information which requires the complement of other techniques.…”
Section: Derived Properties From Light Curves Of Binary/multiple Systemsmentioning
confidence: 99%
“…We provide ephemerides of TNO/Centaurs usable with SPICE library and available at http://www.imcce.fr/~desmars/ research/tno/ The offset observations of the selected TNOs are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/584/A96 Affiliated researcher at Observatoire de Paris/IMCCE, 77 avenue Denfert Rochereau 75014 Paris, France accuracy (Elliot et al 2010;Sicardy et al 2011;Ortiz et al 2012;Braga-Ribas et al 2013) from the resulting light curves of ground-based observers located inside the shadow path or just outside it. This level of accuracy in dimensions can only be rivaled by space missions.…”
Section: Introductionmentioning
confidence: 99%